Editorial Note - Mandal , Prabhat Kumar (Journal of Meat Science, 2022)
I felt honoured when I was chosen again as Chief Editor for the Journal with an Editorial Board comprising of young and dynamic scientists in November, 2016 in Ludhiana. We are happy to bring out the new issue of JMS (Vol-12, issue-2) within time. The New Editorial Board started functioning since April, 2017 and this is the first issue to be published with new editors.I am extremely happy to inform you that our Journal of Meat Science (J299) has got a new 2018-NAAS score of 4.22 w.e.f. 01.01.2018. I wish to thank all of you for your support and congratulate our team of EC-IMSA and EB-JMS. Earlier we resolved to improve the Journal further by making it fully available online to increase the accessibility and thereby increase citation of our papers, and the NAAS score. We are glad to publish the current issue in both print and online version (www.indianjournals.com). To further increase the NASS Score I request all our members to submit your quality work to JMS and please try to cite our papers from JMS to the maximum extent possible in all your manuscript submitted to JMS or any other Journal.I also request our authors to strictly follow the JMS guidelines and format of the Journal before submission. On behalf of the Editorial board I wish to convey my sincere thanks to all the authors for their cooperation. My sincere thanks are also due to all the Associate Editors and Members of EB and the reviewers who have spent their valuable times in reviewing /editing the manuscripts. I specially thank Dr.Naveena, B.M., Editor, JMS and Dr. Muthukumar, Secretary, IMSA for their help in final stages for theprinting of the Journal from the Head Quarter. Soliciting your whole hearted cooperation.